Removal of Emulsified Oils in Contaminated Water by Air Flotation and Filtration Techniques - Erdeni, Abid Ahmad (Journal for Research in Applied Sciences and Biotechnology, 2023)
The study was conducted for the purpose of removing the emulsion oils that polluted water, as a processing unit was designed and manufactured by the researcher, the two phases included a basin for the air flotation to separate the emulsion oil in the water. For the purpose of removing the remaining water polluted oil, and samples were taken after (10,20,40) minutes to test the effect of time in the treatment method with air, as well as samples after nominating the candidates to test their efficiency. The results demonstrated the efficiency of both the flotation basin with air and two filters high efficiency in removing the emulsion polluted water, as it was the highest efficiency of the flotation basin at 40 minutes and the removal rate was 98. 33 %, as well as the candidates have proven efficiency in removing the remaining oil from the bundle of cavity, and that the highest removal rate is (96, 100) %, respectively, for both sponge filter and Eucalyptus powder filter, and this is confirmed by the results of the concentration of Turbidity.